Pengaruh Kesadaran Wajib Pajak, Pengetahuan Pajak, Dan Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Alvina Ramadhan; Sri Nitta Crissiana Wirya Atmaja (GLOBAL SCIENTS PUBLISHER, 2024)
This study analyzes the effect of taxpayer awareness, tax knowledge, and fiscus service on the compliance of motor vehicle taxpayers at SAMSAT Balaraja. This research uses a quantitative approach with primary data collected through questionnaires from registered taxpayers. The sample consists of 100 respondents selected using the incidental sampling method. Data analysis was conducted using multiple linear regression with SPSS version 27 software. The results show that taxpayer awareness, tax knowledge, and fiscus service have a significant effect, both simultaneously and partially, on the compliance of motor vehicle taxpayers. The Adjusted R-square value reveals that these variables explain 33.0% of the variation in motor vehicle taxpayer compliance, while the remaining 67.0% is influenced by other factors outside the scope of this study. This research emphasizes the importance of improving awareness, education, and service quality to enhance motor vehicle taxpayer compliance